Assessing and planning city region food system: Colombo (Sri Lanka) synthesis report - Food and Agriculture Organization of the United Nations; International Water Management Institute (Food and Agriculture Organization of the United Nations, 2018)
This report is the result of the implementation of an assessment methodology for Colombo and its city region food system (CRFS). Colombo stands as a unique city in Sri Lanka due to the complexity of its socio-demographic profile and the diverse food items that arrive through multiple channels. The busy and complex lifestyle of its inhabitants, together with the floating population of the city, creates a high demand for catering services that supply prepared food for direct consumption. In addition, the Colombo Municipal Council (CMC) acts as the national hub for imported food items and the regional hub for vegetable and fruit. As a result, Colombo has one of the most complex food systems in Sri Lanka. The aims of the CRFS assessment include: to better understand the functioning the Colombo food system; to examine the current and future constraints on food security and safety, with respect to the challenges of urban growth, diversity, lifestyle and dynamics; to explore the sustainability and resilience of the Colombo CRFS; and to seek to improve the livelihoods of rural and urban dwellers now and in the future.